2010
DOI: 10.1021/ma9022586
|View full text |Cite
|
Sign up to set email alerts
|

Gyroid-Forming Diblock Copolymers Confined in Cylindrical Geometry: A Case of Extreme Makeover for Domain Morphology

Abstract: The self-assembly of gyroid-forming diblock copolymers confined in cylindrical geometry is studied using a combination of computer simulations and experiments. The simulations, based on a system qualitatively representative of poly (styrene-b-isoprene)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 59 publications
2
65
0
Order By: Relevance
“…Ruotsalainen et al observed lamellar-within-spherical structures for a poly(styrene-b-vinylpyridine) system [119]. Rutledge et al prepared electrospun block copolymers using a co-annular needle system, with the copolymer confined within a shell with a high glass transition temperature [120,121]. The shell served as a process aid for the core material during electrospinning, poly(styrene-b-isoprene-b-styrene), and also confined the copolymer during the subsequent annealing step [120].…”
Section: Fibers Formed From Block Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruotsalainen et al observed lamellar-within-spherical structures for a poly(styrene-b-vinylpyridine) system [119]. Rutledge et al prepared electrospun block copolymers using a co-annular needle system, with the copolymer confined within a shell with a high glass transition temperature [120,121]. The shell served as a process aid for the core material during electrospinning, poly(styrene-b-isoprene-b-styrene), and also confined the copolymer during the subsequent annealing step [120].…”
Section: Fibers Formed From Block Copolymersmentioning
confidence: 99%
“…The shell served as a process aid for the core material during electrospinning, poly(styrene-b-isoprene-b-styrene), and also confined the copolymer during the subsequent annealing step [120]. Gyroid-type structures were formed when the block copolymer poly(styrene-b-dimethyl siloxane) was used with a poly(methacrylic acid) shell [121]. Ma et al reported the formation of superhydrophobic fibers by the electrospinning poly(styrene-b-dimethylsiloxane).…”
Section: Fibers Formed From Block Copolymersmentioning
confidence: 99%
“…For cylindrical pores, experiments show that new morphologies including helical structures and concentric lamellae appear as the diameter of the cylindrical pore changes [5][6][7]. These observations have been verified by numerical simulations, which in turn have predicted structures not yet observed [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 90%
“…The theoretical/numerical approaches that have been used to study copolymers in cylindrical confinement include SCFT [40][41][42][43][44][45], DFT [46], MC [47][48][49][50][51][52][53], SA [30,[54][55][56][57], dissipative particle dynamics [58], coarse-grained molecular dynamics [59] and TDGL theory [60]. These studies have yielded detailed phase diagrams associated with the new morphologies and how these vary with pore diameter, chemical incompatibility and the block asymmetry [1].…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) confinement in the form of cylindrical pores with curved surfaces presents a more tightly confined geometry than that of thin films, and 2D confinements have been demonstrated to provide rich, varied structures. The use of cylindrical nanotubes produces 2D confinement with varying diameters for diblock copolymers as-studied in theory [16][17][18], simulation [19][20][21][22][23][24][25], and experiments [26][27][28][29][30][31]. Previous studies have also shown that the combined effects of confinement and curvature significantly influence the morphologies of copolymers in self-assembled systems.…”
Section: Introductionmentioning
confidence: 99%